Analysis and improvement of the order management process in an automotive company using the DMAIC methodology - Córdova Cifuentes, Abner; ARAGON, LUCY GABRIELA (LACCEI, 2025)
The article addresses the proposal to improve the order management process for spare parts and lubricants in an automotive company, using the DMAIC-Six Sigma methodology. The objective of the work was to address the problems of preventive supply of spare parts and lubricants used for the after-sales service of the trucks of one of the leading brands in the market. During the diagnosis, inefficient waiting times, transportation problems, quality problems, repetitive processes, and lack of ability to calculate the correct rotation were identified. Solutions are proposed such as tabulation of sales and appropriate picks to obtain an adequate order prediction, monitoring transportation to be able to make time regulations and planning training for personnel in the logistics area to carry out correct supply. In summary, the implementation of the DMAIC-Six Sigma methodology allowed us to improve the precision in the orders of spare parts and lubricants that are responsible for preventive maintenance. This has comprehensively solved the problem, allowing demand to be met during the estimated periods, reducing downtime in terms of transportation and optimizing the use of human resources, which translates into higher annual income for the company.